Introduction to biochemistry - Feigenson, Gerald W. (Henry Stewart Talks, 2019)
Matter in the universe, Origin of chemistry, Nuclear reactions, Properties of living systems, Main biomolecules, Metabolism generalities, Importance of enzymes, Amino acid residues, Ionisable groups
Reviewed at 2022/11/27